2014
DOI: 10.1016/j.sbspro.2014.11.107
|View full text |Cite
|
Sign up to set email alerts
|

CSR and Financial Performance Analysis: Evidence from Top ASEAN Listed Companies

Abstract: The purpose of this research is to investigate whether the commitment of companies to their stakeholders has a relationship with better financial results and also to establish the extent and pattern of corporate disclosure in the top listed companies in the ASEAN region. This research found that there is a moderate to strong positive correlation between all the variables when analyzed as a whole. However, the correlation result varies when broken down into individual countries and sectors. There is an increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 37 publications
3
47
0
1
Order By: Relevance
“…The above table shows that, firstly, the disclosure of Economics aspect (EC) has a positive and significant impact on the market performance of the company. These results are consistent and support the research by [6], and [7]. This proves that the disclosure of the economics aspects in sustainability report improve market performance since the disclosure of these aspects can prove their company's contribution to the development of the global economy and local communities.…”
Section: Sustainability Report Disclosuresupporting
confidence: 89%
See 1 more Smart Citation
“…The above table shows that, firstly, the disclosure of Economics aspect (EC) has a positive and significant impact on the market performance of the company. These results are consistent and support the research by [6], and [7]. This proves that the disclosure of the economics aspects in sustainability report improve market performance since the disclosure of these aspects can prove their company's contribution to the development of the global economy and local communities.…”
Section: Sustainability Report Disclosuresupporting
confidence: 89%
“…However, several studies related to the sustainability report showed inconsistent results. Research by [6], as well as [7] states that the three aspects of sustainability report has a significant positive effect on the enterprise market performance, either partially or simultaneously. On the other hand, research by [8] expressed a negative influence on such things.…”
Section: Introductionmentioning
confidence: 99%
“…Those score will be summed then subtracted with number of criterias in GRI 3.1. This measurement also used in Jenkins & Yakovleva (2006), Yuliana et al (2008; Panayiotou et al (2009), Mulyadi & Anwar (2012, Waworuntu et al (2014). ISSN 2162-4860 2016 www.macrothink.org/ber 56 The higher CSR score, indicate that more firm's CSR activity fulfil GRI's criteria.…”
Section: Methodsmentioning
confidence: 99%
“…However, despite the pervasive organizational rhetoric, there is mixed evidence regarding the empirical relationship between reputation and CSR activity (Graafland, 2017;Inoue, Kent, & Lee, 2011;Nelling & Webb, 2009;Pava & Krausz, 1996;van Beurden & Gössling, 2008;Waworuntu, Wantah, & Rusmanto, 2014). This study focuses specifically on measurement issues in the highly touted, yet empirically contested, CSR performance/reputation link.…”
Section: Introductionmentioning
confidence: 99%